Approach to the definition of religion in Constenla-Umaña, in his books and articles compiling Costa Rican indigenous texts - Solano-Fallas, Andrés (2026)
The article aims to make a conceptual approximation of what Adolfo Constenla-Umaña (Costa Rican linguist (1948-2013) who researched indigenous languages) understood about “religion”, because it is a concept that appears constantly in his analysis, when it deals with indigenous literature, but that he did not expressly define, according to what can be inferred from the review of the primary sources and secondary literature that has been written about the author. In what corresponds to the methodological, an approach typical of analytical philosophy is carried out, in which different texts by Constenla-Umaña are carefully scrutinized in which the author made reference to matters related to religion, religion, religious practices or customs. The systematization of the information was structured in a series of questions, which starts from the basics, advancing to other related issues. As results, three aspects were concluded: the first, that Constenla-Umaña avoids falling into an a priori evaluative judgment, by moving away from attempts to classify religion in binomial terms of “good-bad”; second, it also avoids reproducing unnecessary questions about whether certain elements of religion are real or fictitious; and the third, that it shows a deep respect that the author had for religion, specifically for indigenous religions.